Spacetime Metamaterials-Part II: Theory and Applications - Caloz, Christophe; Deck-Leger, Zoe-Lise (IEEE transactions on antennas and propagation, 2020)
The overall article presents the authors' vision of the emerging field of spacetime metamaterials, and related systems, in a cohesive and pedagogical perspective, systematically building up the physics, modeling, and applications of these media upon the foundation of their pure-space and pure-time counterparts. Following the first part, dealing with the general concepts underpinning spacetime metamaterials, this part establishes the theory of spacetime metamaterials and overviews some of their current and potential applications. It first describes the scattering phenomenology of a spacetime interface, the building brick of any spacetime metamaterial, and deduces the corresponding electromagnetic boundary conditions. Upon this basis, it derives the spacetime interface scattering (Fresnel-like) coefficients and frequency transitions, and subsequently generalizes time reversal to spacetime compansion (compression and expansion). Then, it illustrates the new physics of spacetime metamaterials with the examples of spacetime mirrors and cavities, the inverse prism and chromatic birefringence, and spacetime crystals. Next, it discusses various applications-categorized as frequency multiplication and mixing, matching and filtering, nonreciprocity and absorption, cloaking, electromagnetic processing, and radiation. Finally, the conclusion section provides a list of eight items that concisely summarizes the key results of this article, in completion to the list related to the general concepts in Part I.